APLIKASI NUTRINEEDS DALAM PENENTUAN KEBUTUHAN KALORI HARIAN BAGI PENDERITA DIABETES MELITUS - Oktavianti, Siti Ayu; Divayana, Yoga; Raka Agung, I Gusti Agung Putu (Jurnal SPEKTRUM, 2021)
In this journal, an analysis of the NutriNeeds application is carried out. The Nutrineeds application is the result of a study that aims to determine daily calorie needs for people with diabetes mellitus. The level of accuracy of the NutriNeeds application will be compared with the Broca method in determining the daily calorie requirements for people with diabetes mellitus. The NutriNeeds application is designed with the mamdani fuzzy inference system and android studio, which uses 7 inputs in the fuzzy inference system, namely gender, male BBI, female BBI, age, BMI, physical activity, stress factors, and produces an output, namely calories daily. The NutriNeeds application requires data input, namely gender, weight, height, age, and physical activity, which will display daily calorie results and meal schedules. The data in this study were 5 pieces of data on patients with diabetes mellitus. Based on the comparison of daily calories generated by the NutriNeeds application by calculating daily calories using the Broca method, the results of the calculation of the percentage of accuracy obtained a MAPE value of the NutriNeeds application of 1.1% which is classified as very accurate.